Modernization, Postmodernism and Religion: New challenges and Opportunities - Ganbarov, Asaf (Scholarya Demo Journal of Ruby, 2019)
This article deals with the relationship between religion and modernity intheoretical perspective which is one of the actual problems of sociology ofreligion. The main purpose of the article is to identify the effects of the modernization process and postmodernism on religion. Thus, the main featuresof modern society rationalization, individualism, industrialization, institutional differentiation processes have been explored and the effects ofmodernization on religion in multidimensional aspects are examined. The process of modernization consists of a transition from a traditional agrarian society to a modern industrial society as well as a combination of technological, economic, social, cultural and political changes aimed at the modernization of the sociopolitical system. In general, four aspects of the modernization andreligion are distinguished: secularization, adaptation, conservatism and innovation. The secularization of society, which means the decline of religion, is merely one aspect of the relationship between religion and modernity, thus, modernization of society does not necessarily result in the loss of importance of religion in modern society. It is also worth noting that the development of postmodernist thought in modern world creates new opportunities for religiousand mystical ideas that are not based on rational and accurate scientific methods. Thus, religious beliefs are gradually beginning to revive as an alternative worldview in postmodern society.